League-table incentives and price bubbles in experimental asset markets - Stephen L. Cheung; Andrew Coleman (Institute for the Study of Labor (IZA), 2011)
We study experimental markets in which participants face incentives modeled upon those prevailing in markets for managed funds. Each participant's portfolio is periodically evaluated at market value and ranked in a league table according to short-term paper returns. Those who rank highly attract a larger share of new fund inflows. Under conditions in which prices are close to intrinsic value, the effect of incentives is mild. However under conditions in which markets are prone to bubble, mispricing is greatly exacerbated by incentives. Even in experienced markets, prices climb to levels clearly indicative of speculation and do not always crash back.
urn:nbn:de:101:1-201105306270
Keywords: C92; G12; M52; 330; league tables; price bubbles; managed funds markets; tournament incentives; asset market experiments